2017
DOI: 10.1167/iovs.17-22506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neovascular Lesion Area Measurements From Different Swept-Source OCT Angiographic Scan Patterns in Age-Related Macular Degeneration

Abstract: PurposeWe compared area measurements for the same neovascular lesions imaged using swept source optical coherence tomography angiography (SS-OCTA) and enlarging scan patterns.MethodsPatients with neovascular age-related macular degeneration were imaged using a 100-kHz SS-OCTA instrument (PLEX Elite 9000). The scanning protocols included the 3 × 3, 6 × 6, 9 × 9, and 12 × 12 mm fields of view. Two groups were studied. Group 1 included small lesions contained within the 3 \begin{document}\newcommand{\bialpha}{\bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The currently available and reproducible[ 8 ] methods for the quantification of CNV characteristics rely on semiautomatic software to define the CNV area and its boundaries, enabling the CNV to be followed up along the course of the disease. [ 9 ] Recent studies have demonstrated that the application of fractal dimension (FD) analysis may be useful in differentiating blood flow in the quiescent, active and remission phases of the disease. [ 10 ] Other studies have suggested that lacunarity (LAC) or junction density could be an objective way of following and managing CNV.…”
Section: Introductionmentioning
confidence: 99%
“…The currently available and reproducible[ 8 ] methods for the quantification of CNV characteristics rely on semiautomatic software to define the CNV area and its boundaries, enabling the CNV to be followed up along the course of the disease. [ 9 ] Recent studies have demonstrated that the application of fractal dimension (FD) analysis may be useful in differentiating blood flow in the quiescent, active and remission phases of the disease. [ 10 ] Other studies have suggested that lacunarity (LAC) or junction density could be an objective way of following and managing CNV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that OCT-A is able to show the minimal CNV surface 25 and is reproducible for accurate evaluation of CNV blood flow area. 26 Miere et al have recently demonstrated a reduction in CNV surface area in treatment-naïve eyes after the loading dose of three monthly IVI of anti-VEGF. 27 Our results agree with these findings, as we demonstrated a blood flow area reduction after the loading dose.…”
Section: Discussionmentioning
confidence: 98%
“…38 This imaging device, which operates at 100,000 Ascans/s and is equipped with a SS tunable laser with center wavelength between 1040 and 1060 nm, delineates motion contrast signals using optical microangiography (OMAG) algorithm. 39 Sequential B-scans were obtained at a fixed position, followed by the calculation of variations in both intensity and phase information. Side-by-side B-scans allowed for the construction of three-dimensional OCTA images.…”
Section: Ss-oct and Octa Imagesmentioning
confidence: 99%